Analisis Preminery Research Phase Sebagai Dasar Pengembangan LKPD Biologi Berbasis PBL - Diana Molly; Nurul Fauziah; Nurkhairo Hidayati (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This research aims to explore the role and importance of Student Worksheets (LKPD) in the learning process at primary and secondary education levels. LKPD as a learning aid serves to increase student involvement, facilitate understanding of concepts, and measure learning progress. Using qualitative methods, this research collects data through observation, interviews and document analysis from various schools. The research results show that effective implementation of LKPD can increase student learning motivation and provide constructive feedback for teachers. LKPD not only functions as a means of evaluation, but also as a reflection tool for students to develop critical and creative thinking skills. Therefore, this research emphasizes the need for integration of LKPD in the curriculum to support more effective and student-oriented teaching.